2017
DOI: 10.1248/yakushi.17-00078
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Hay Fever and Mineral Concentration in the Hair, Lifestyle or Aging

Abstract: It is important to ingest just proportions of minerals to prevent disease, but these minerals are also secreted into the hair. Meanwhile, the number of hay fever patients in Japan is increasing, causing an increase in national medical expenses. In this study, we investigated the relationship between hay fever and mineral concentrations in hair to obtain ndings on the risk of developing pollen allergies. A questionnaire survey was conducted for 275 men and 977 women on their lifestyle habits and ten kinds of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Accordingly, hair minerals should be measured to better understand the risks for the development of certain health conditions. Previous studies have demonstrated an association between the risk of hay fever and low concentrations of iron, Ca, chromium, and cadmium, and high concentration of selenium in hair 5) ; an association between schizophrenia and low concentrations of Zn and Ca and high concentrations of Cu and cadmium in the hair of adult men 6) ; and a relationship between low concentrations of Zn in hair during childhood and autism spectrum disorder 7) . Therefore, measurement of hair mineral concentrations during regular haircuts may contribute to the early detection of diseases and improve health consciousness.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, hair minerals should be measured to better understand the risks for the development of certain health conditions. Previous studies have demonstrated an association between the risk of hay fever and low concentrations of iron, Ca, chromium, and cadmium, and high concentration of selenium in hair 5) ; an association between schizophrenia and low concentrations of Zn and Ca and high concentrations of Cu and cadmium in the hair of adult men 6) ; and a relationship between low concentrations of Zn in hair during childhood and autism spectrum disorder 7) . Therefore, measurement of hair mineral concentrations during regular haircuts may contribute to the early detection of diseases and improve health consciousness.…”
Section: Introductionmentioning
confidence: 99%